OP85 Do Good Health and Material Circumstances Protect Older People from the Increase in Mortality after Bereavement?. (17th September 2012) - Shah, S M; Carey, I M; Harris, T; DeWilde, S; Victor, C R; Cook, D G
Abstract : Background: Death of a spouse or partner is a common major life event for older people. The adverse health effects of bereavement are well recognised with an increased risk of death described in several populations. The impact of modifying factors, such as chronic disease and material circumstances, is less well understood. In this study, we use a large UK primary care database to examine the modifying and mediating effect of physical comorbidity and material socio-economic circumstances on the rise in mortality in the first year after bereavement. Methods: We identified 171, 120 older (60 years and over) couples in a UK primary care database (THIN) based on a shared household identifier. The couples were followed up between 2005 and 2010 for an average of 4 years. 26, 646 (15.5%) couples experienced bereavement with mean follow up after bereavement of 2 years. The effect of bereavement on risk of death in the surviving partner was examined in a survival model adjusted for age, sex, comorbidity at baseline, material deprivation based on area of residence, season and smoking. Further analysis examined the effect of changes in comorbidity during follow up. Results: The fully adjusted hazard ratio (HR) for bereavement in the first year after bereavement was 1.25 (95% CI: 1.18 to 1.33). Further adjustment for changes in comorbidity throughout follow up did not alter the hazard ratio for bereavement (HR 1.27, 95% CI: 1.19 to 1.35). The effect of bereavement was not modified by age, gender or baseline comorbidity. The relative rise in mortality after bereavement was greatest in individuals with no significant chronic comorbidity throughout follow up (HR 1.50, 95% CI: 1.28 to 1.77) and in more affluent couples ( P =0.035). Conclusion: We have confirmed the increased risk of mortality after bereavement and demonstrated its independence of pre-existing physician recorded chronic comorbidity and social status. Our analysis, taking account of changes in morbidity before and after bereavement, suggests that the rise in mortality after bereavement is not primarily mediated through new or worsening chronic physical disease. Furthermore, there was no evidence that pre-existing or continuing good health or affluence protect individuals. The results also suggest that, paradoxically, good health and high social status may accentuate the rise in mortality after bereavement. Our findings suggest that the rise in mortality after bereavement acts as a leveller, affording no protection to the affluent or healthy, and is best explained by an increase in sudden unexpected deaths.